Effect of dietary organic and inorganic selenium supplementation on chemical, mineral and fatty acid composition of ostrich meat. Issue 1 (2nd January 2016) - Poławska, Ewa; Zdanowska-Sąsiadek, Żaneta; Horbańczuk, Jarosław; Pomianowski, Janusz Franciszek; Jóźwik, Artur; Tolik, Dominika; Raes, Katleen; De Smet, Stefaan
Abstract : This study evaluated the effect of dietary organic and inorganic selenium supplementation on chemical, mineral and fatty acid composition of ostrich meat. Forty ostriches were raised in two groups (OSe and IOSe, diets supplemented with an organic form and an inorganic form of selenium, respectively). The form of selenium had no influence on chemical composition of ostrich muscle. Although, there were no significant differences in total content of SFA, MUFA and PUFA, the content of LA and EPA was higher in the muscles of ostriches which were put on a diet supplemented with an organic form of selenium, what resulted in lower n-6/n-3 fatty acids ratio in OSe group (9.99) in comparison to IOSe group (11.70). The results of the study indicate that dietary organic selenium supplementation improves the quality of the ostrich meat as related to the health promoting properties (LA, EPA and selenium content) of meat.